ANALYSIS OF THE NEEDS FOR DEVELOPING AN AUGMENTED REALITY-BASED ECOSYSTEM MODULE ASSISTED BY ASSEMBLR APPLICATION FOR GRADE V ELEMANTARY SCHOOL - Tsaqifa Taqiyya Ulfah (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
Technology is developing very rapidly and has an impact on all aspects, one of which is education. Based on these conditions, teachers must be able to conduct learning that is adaptive to technology. One of the utilization of technology in learning is learning media. IT-based learning media is very popular with students because it looks attractive and facilitates student understanding when learning. However, based on the facts, the utilization of IT media is not optimal. Based on these problems, this study aims to analyze the needs of AR-based module development assisted by the Assemblr application. Researchers use the Thiagarajan Model R&D method which is limited only to the first stage, namely the defining stage which focuses on analyzing needs before making products. The data accumulation used by researchers is interviews, observations, and filling out online questionnaires. The results showed that 1) Students are already proficient in using cellphones and are very dependent on gadgets. 2) Students like science learning on ecosystem material. 3) Students like colorful media such as videos. 4) The school does not have its own module. 5) Teachers and students are not familiar with Augmented Reality technology. 6) Learning media that is often used package books and PPT so that it is less varied. Keywords: Needs Analysis, Learning Media, Augmented Reality